Accuracy of the combination of commercially available biomarkers and cervical length measurement to predict preterm birth in symptomatic women: A systematic review. (March 2021) - Dehaene, I.; Lorthe, E.; Gurney, L.; Turtiainen, P.; Schwickert, A.; Svenvik, M.; Care, A.; Bergman, L.; ,
Abstract: An accurate prognostic method for preterm birth (PTB) could avoid unnecessary treatment(s) with potentially negative effects. The objective was to explore the prognostic accuracy of commercially available bedside cervicovaginal biomarker tests in combination with cervical length (CL) compared to CL measurement alone and/or a biomarker test alone, for PTB within 7 days after testing symptomatic women at 22–34 weeks. The MEDLINE, Cochrane, Embase and Web of Science databases were searched from inception to August 28th, 2019. Seven hundred and eight articles were identified and screened using Rayyan. Studies reporting on the predictive accuracy of combined tests compared to CL or biomarker alone for the prediction of PTB within 7 days of testing in symptomatic women with intact membranes were included. A piloted data extraction form was used. Direct comparisons of the prognostic accuracy of the combination test with CL measurement or a biomarker alone were done, as well as comparisons of prognostic accuracy of the included combination tests (indirect comparisons). Twelve articles were included (seven on fetal fibronectin, four on phosphorylated insulin-like growth factor binding protein-1, one comparing both). A variety of CL cut-offs was reported. The results could not demonstrate superiority of a combination method compared to single methods. Due to data scarcity and quality, the superiority of either predictive test for PTB, either combination or single, cannot be demonstrated with this systematic review. We recommend further research to compare available biomarkers.